Authority of a Female Cleric in the Educational Sphere (A Study of Nyai Khairiyah Hasyim’s Leadership) - Imas Nur Kholida (Yinyang: Jurnal Studi Islam Gender dan Anak, 2024)
This research project aims to explore the relationship between piety, initiative, and the process of self-empowerment in a female cleric, drawing on Saba Mahmood’s theory of piety. The empirical evidence is based on ethnographic research into the transformation of Nyai Khairiyah Hasyim’s religious authority. This article presents two key propositions. First, it analyzes the transformation of Nyai Khairiyah Hasyim, who promoted Islamic boarding school education and became the first female school instructor in the city of Makkah. Second, it examines how her contributions and fatwas have brought about significant shifts in the perception of women in public spaces within a maledominated society. By reflecting on her personal experiences and efforts as a woman and cleric rooted in Islamic boarding school traditions, she has demonstrated a depth of knowledge and insight that challenges the notion of formal diplomas. Her fatwa products include allowing female students to wear hijabs during marching activities, innovating the rubu’ hijab model, and advocating for the family planning (KB) program.